Drag reduction of biopolymer flows - Jaafar, A (2010)
Drag reduction of rigid and semi-rigid biopolymers – scleroglucan (0.005% and 0.01% w/w) and xanthan gum (0.0124% and 0.07% w/w) – in a circular pipe and a concentric annular pipe (radius ratio  = 0.5) have been investigated experimentally. The objective here is to assess and study the behaviour of these polymers and compare to the drag reduction by flexible polymers, available in the literature. Pressure-drop, mean axial and complete Reynolds normal stress data measurements on the polymer solutions were conducted using laser Doppler anemometry. Measurements were also performed on the Newtonian solvent (water) for comparison. Rheological characterization of the polymers conducted over a wide range of concentrations (0.005% - 0.75% w/w) showed increased shear-thinning ability of the polymer solutions with increasing solution concentration. The pressure-drop measurements indicate that the effectiveness of these polymers as drag-reducing agents is only mildly dependent on the Reynolds number. Qualitative assessment of the turbulent peak values in the circular pipe flow shows behaviour resembling that of low drag-reducing (DR 40%) flexible polymer solutions data available in the literature such as carboxymethylcellulose with increases in u'+ and decreases both in w'+ and v'+ generally when compared to that of the Newtonian flow at the same Reynolds number. The peak values of the turbulent fluctuation levels (normalized with UB) in the annular pipe, however, shows a decreasing trend of the axial component below 40% drag reduction. Above this drag-reduction “limit”, the peak levels seemed to increase, generally, with drag reduction. Decrease in both w'/UB and v'/UB when compared to that of the Newtonian flow are observed at the same Reynolds number for all drag-reducing flows, similar to what is observed in the pipe-flow study.